The UN Framework on Business and Human Rights: A Workers’ Rights Critique - Venkatesan, Rashmi (2019)
The “Protect, Respect, Remedy” Framework along with the UN Guiding Principles on Business and Human Rights is the current global standard regarding corporate conduct. This article analyses the UN Framework from the vantage point of labour rights in India by looking at the garment supply chain. It argues that it can do little to induce states and businesses to bring substantive improvements to working conditions in a largely informal economy like India. Without the state performing its duty to protect human rights, the secondary responsibility of corporations can do very little in realising the rights of workers. Nonetheless, its tallest contribution is that it has given a platform for civil society to push for better conduct from all businesses and marks the beginning of a unified international business and human rights agenda.
Keywords: India; Garment sector; supply chains; labour rights; UN Guiding Principles